Non-sebaceous lymphadenoma of the submandibular gland: diagnostic challenges in the head and neck cancer pathway - Garside, Graham (BMJ Case Rep, 2020)
Non-sebaceous lymphadenoma (NSLA) is a rare benign salivary gland tumour with lymphoid and epithelial components and without sebaceous differentiation. The large majority of the reported cases arise within the parotid gland. We present an NSLA arising from the submandibular gland. The tumour presented as a painless longstanding neck lump. Ultrasound, fine needle aspiration, MRI and positron emission tomography found features supportive of squamous cell carcinoma. The patient was treated with surgery for oropharyngeal carcinoma of unknown origin, in accordance with local and national guidelines. The final histological assessment revealed the level Ib neck lesion to be NSLA. Although a rare occurrence, these lesions may pose a diagnostic challenge in the head and neck cancer pathway.